Educação ambiental e saneamento básico no âmbito escolar em João Pessoa – Paraíba - Silva Filho, Emmanoel Paulino da (2013)
The implementation of strategies aimed at awakening of environmental knowledge in schools with the children and adolescents manifests itself as an efficient strategy for long-term results. Instilling in students' everyday actions that require the awakening of environmental consciousness either through educational workshops, whether through games is an activity that can only develop through patience and continuity. The objective was to diagnose the perception of students on Environmental Education (EE) and Sanitation (SB); investigate the conception of students on educational activities after EA; check with the community to apply for school projects and EA SB; promote awareness of learners in EA through playfulness and verifying the design of educators on the environment, EA and SB. The research was conducted in two schools in the municipal schools of João Pessoa, in the neighborhoods of Christ Redeemer and Mangabeira during the year 2012 as the theme Environmental Education and its close relationship with the efficient provision of Sanitation. The characteristic methodology used was a qualitative approach, pointing out features of ethnographic research, phenomenological, of bioregionalism and participant observation. Therefore, it employed the use of questionnaires pre-and post-test to the students and the teachers and the community just a questionnaire. With students from both schools have developed five workshops teaching the sixth to ninth years based techniques reuse of recyclable materials. In two schools it was found that the majority of respondents initially indicated a generalist view of EA and after the workshops the students increased their understanding recognizing the vision conservation, among others. The communities had a low level of environmental knowledge, but a good degree on factors plumbing their respective localities and teachers of the two schools have embraced the research objectives and reinforcing explanations of educational workshops, contributing to the development. The majority asserted that could generally apply their knowledge in EA, in everyday life, and also positively as often relate the content of their disciplines with EA. We conclude that students' knowledge, about the environmental and health issues, noted after developments in various aspects of research and development activities that escape the routine of students who break the sameness of the traditional model of education, with explanations differentiated view videos, and development of pedagogical workshops intending to raise awareness on environmental issues, fulcrum those that refer to health services, are quite valid before the degree of motivation aroused.